The Life-Cycle Profile of Time Spent on Job Search - Aguiar, Mark; Hurst, Erik; Karabarbounis, Loukas (American Economic Review, 2013)
Using time use survey data we document a hump-shaped profile of job search time in the United States across the life-cycle. The middle-aged unemployed spend roughly three times as much time in job search as the youngest group of unemployed. The hump-shaped profile of job search time is relatively stable across demographic groups. However, the profile of job search time appears to be declining in non-US countries. We discuss how standard life-cycle models with incomplete markets have difficulty in accounting for the hump-shaped profile found in the US data.